2015
DOI: 10.1083/jcb.201506048
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin ligase TRIM3 controls hippocampal plasticity and learning by regulating synaptic γ-actin levels

Abstract: TRIM3 regulates synaptic γ-actin levels. TRIM3-deficient mice consequently have higher hippocampal spine densities, increased long-term potentiation, and enhanced contextual fear memory consolidation, indicating that temporal control of ACTG1 levels by TRIM3 is required to constrain hippocampal plasticity within physiological boundaries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 74 publications
0
23
0
Order By: Relevance
“…For analysis of the images and quantification of synaptic GluA2 expression the Columbus image storage and data analysis system (PerkinElmer; Waltham, MA) was used. The experiment was independently replicated ( Schreiber et al, 2015 ) with a similar set-up from a different culture using independent sets of animals, and the resulting 2 × 5 wells were taken as the final n-number.…”
Section: Methodsmentioning
confidence: 99%
“…For analysis of the images and quantification of synaptic GluA2 expression the Columbus image storage and data analysis system (PerkinElmer; Waltham, MA) was used. The experiment was independently replicated ( Schreiber et al, 2015 ) with a similar set-up from a different culture using independent sets of animals, and the resulting 2 × 5 wells were taken as the final n-number.…”
Section: Methodsmentioning
confidence: 99%
“…The UPS targets proteins for proteolysis through the conjugation of ubiquitin to substrates, which is coordinated by E3s ( 16 ). INO80 was previously identified as a substrate of TRIM3, an E3 that has been implicated in hippocampal synaptic plasticity and memory ( 21 ). Following extended-access cocaine self-administration, we found a decrease in TRIM3 protein expression in NAc P1 fractions on AD30 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, viral-mediated manipulation of INO80 bidirectionally mediated the expression of cocaine craving on AD30. We then examined E3 ubiquitin ligase (E3) tripartite motif-containing protein 3 (TRIM3), of which INO80 is a substrate ( 21 ). We found that TRIM3 protein expression and interaction with INO80 are decreased on AD30, indicating that the ubiquitin-proteasomal regulation of INO80 is impaired during prolonged abstinence from cocaine.…”
Section: Introductionmentioning
confidence: 99%
“…Also in sensory neurons, GFP mRNA containing the 3′ UTR of Actβ translocates into axons, whereas the 3′ UTR of Actγ cannot drive the transport of GFP mRNA into axons (Willis et al, 2007Donnelly et al, 2011). However, in more recent studies using sensitive techniques, mRNAs for Actγ could be detected in hippocampal synapse-enriched fractions, and mRNAs for both Actα and Actγ were detected in neuropil and somata layers of the CA1 region of the hippocampus (Cajigas et al, 2012;Schreiber et al, 2015). Knockout mouse models for the different actin isoforms have provided evidence both for their specific and overlapping cellular functions.…”
Section: Discussionmentioning
confidence: 99%